Thermal performance of axial air cooling system with bionic surface structure for cylindrical lithium-ion battery module. (November 2020) - Yang, Wen; Zhou, Fei; Zhou, Haobing; Liu, Yuchen
Highlights: The novel radiator with bionic surface structure is proposed and applied to battery module cooled by an axial air-cooled BTM system. The cooling performance of the battery module is enhanced when the inlet velocity of air increases, but the power consumption increases obviously. The novel radiator thickness and the bionic surface structure height can effectively reduce the maximum temperature and the temperature difference of battery module. When the optimal parameters of the bionic surface structure are used, the air cooling effect of the battery is the best. Abstract: In order to enhance the cooling performance of air, a new type of radiator with bionic surface structure is proposed and applied to a cylindrical lithium-ion power battery pack with axial air cooling in this paper. The computational fluid dynamics (CFD) model of the battery module is established to study the effect of the inlet velocity and structure parameter of radiator with bionic surface structure on the cooling performance. It is found that when inlet velocity is higher than 0.8 m.s −1, the maximum temperature and the temperature difference of the battery module can be maintained within 308 K and 5 K during the 3 C discharge rate, respectively. Then, four structure parameters (thickness, shape, height, and length) of the radiator with bionic surface structure are optimized by the single factor analysis and the orthogonal test to enhance cooling performance and reduce power consumption. The results show that the thickness of plate is the most important parameter influencing the cooling performance and power consumption. Then, the height of bionic surface structure is the secondary parameter, and the shape of bionic surface structure is the parameter with a minimal impact on the BTMS. The best cooling performance can be obtained when the four structure parameters are 0.4 mm, trapezoid, 1 mm, and 61 mm, respectively. As compared with the original radiator, the temperature difference and power consumption of the optimized battery module are reduced by 8.1 % and 15.54 %, respectively, while the maximum temperature varies a little. The optimal case in this research can be widely applied to enhance the cooling performance in air-cooled BTMS.